Juvenile hormone receptors in insect larval epidermis: identification by photoaffinity labeling. - Palli, S R (1990)
Tritiated photoaffinity analogs of the natural lepidopteran juvenile hormones, JH I and II [epoxy[3H]bishomofarnesyl diazoacetate ([3H]EBDA) and epoxy[3H]homofarnesyl diazoacetate ([3H]EHDA)], and of the JH analog methoprene [[3H]methoprene diazoketone ([3H]MDK)] were synthesized and used to identify specific JH binding proteins in the larval epidermis of the tobacco hornworm (Manduca sexta). EBDA and EHDA specifically photolabeled a 29-kDa nuclear protein (pI 5.8). This protein and a second 29-kDa protein (pI 6.0) were labeled by MDK, but excess unlabeled methoprene or MDK only prevented binding to the latter. These 29-kDa proteins are also present in larval fat body but not in epidermis from either wandering stage or allatectomized larvae, which lack high-affinity JH binding sites. A 29-kDa nuclear protein with the same developmental specificity as this JH binder bound the DNA of two larval endocuticle genes. A 38-kDa cytosolic protein was also specifically photolabeled by these photoaffinity analogs. The 29-kDa nuclear protein is likely the high-affinity receptor for JH that mediates its genomic action, whereas the 38-kDa cytosolic protein may serve as an intracellular carrier for these highly lipophilic hormones and hormone analogs.